THE ROLE OF SOCIAL MEDIA ALGORITHMS IN SHAPING AND CONFLICT RESOLUTION - Latuheru, Rido Dominggus; Cangara, Hafied (Universitas Gunadarma, 2024)
This research aims to explore the dual role of social media algorithms in conflict formation and resolution. Using a systematic literature review method, this research analyses how algorithms can amplify polarization and spread misinformation, as well as their potential to be leveraged in mitigating conflict and promoting constructive dialogue. The results show that algorithms designed to maximise user engagement often contribute to conflict escalation through the formation of